Impact of folate supplementation on the efficacy of sulfadoxine/pyrimethamine in preventing malaria in pregnancy: the potential of 5-methyl-tetrahydrofolate. - MOLLOY, ANNE (My University, 2014)
Malaria remains the leading cause of mortality and morbidity in children under the age of 5 years and pregnant women. To counterbalance the malaria burden in pregnancy, an intermittent preventive treatment strategy has been developed. This is based on the use of the antifolatesulfadoxine/pyrimethamine, taken at specified intervals duringpregnancy,andreportsshowthatthisapproachreducesthemalariaburdeninpregnancy.Pregnancyisalso associated with the risk of neural tube defects (NTDs), especially in women with low folate status, and folic acid supplementation is recommended in pregnancy to lower the risk of NTDs. Thus, in malaria-endemic areas, preg- nant women have to take both antifolate medication to prevent malaria and folic acid to lower the risk of NTDs. However,theconcomitantuseoffolateandantifolateisassociatedwithadecreaseinantifolateefficacy,exposing pregnant women to malaria. Thus, there is genuine concern that this strategy may not be appropriate. We have reviewedworkcarriedoutonmalariafolatemetabolismandantifolateefficacyinthecontextoffolatesupplemen- tation. This review shows that: (i) the folate supplementation effect on antifolate efficacy is dose-dependent, and folic acid doses required to protect pregnant women from NTDs will not decrease antifolate activity; and (ii) 5- methyl-tetrahydrofolate, the predominant form of folate in the blood circulation, could be administered (even at high dose) concomitantly with antifolate without affecting antifolate efficacy. Thus, strategies exist to protect pregnant women from malaria while maintaining adequate folate levels in the body to reduce the occurrence of NTDs.
PUBLISHED
Keywords: folate; folate; International Development